2012
DOI: 10.4236/ns.2012.412126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of myocardial perfusion scintigraphy and computed tomography (CT) angiography based on conventional coronary angiography

Abstract: Coronary artery disease is one of the most common and important health problems in the world. Early diagnosis of this disease is very important to treat before severe myocardial damage occurred. Myocardial perfusion scintigraphy (MPS) and computed tomography coronary angiography (CTCA) which evaluates regional myocardial perfusion and coronary arteries, respectively, are reliable and non-invasive methods in terms of coronary artery disease. In this study we aimed to compare MPS and CTCA based on conventional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In cardiac SPECT, the most commonly used radiotracers are thallium-201 ( 201 Tl) and technetium-99m ( 99m Tc) labeled agents such as sestamibi and tetrafosmin. According to the literature, the sensitivity, specificity, and accuracy of cardiac SPECT varies from 71% to 98%, 33% to 89%, and 72% to 95%, respectively [ 22 , 23 ].…”
Section: A Comparison Of Various Filters In Cardiac Spect: Studiesmentioning
confidence: 99%
“…In cardiac SPECT, the most commonly used radiotracers are thallium-201 ( 201 Tl) and technetium-99m ( 99m Tc) labeled agents such as sestamibi and tetrafosmin. According to the literature, the sensitivity, specificity, and accuracy of cardiac SPECT varies from 71% to 98%, 33% to 89%, and 72% to 95%, respectively [ 22 , 23 ].…”
Section: A Comparison Of Various Filters In Cardiac Spect: Studiesmentioning
confidence: 99%
“…[2225] Different authors and different manufactures suggested different filters. [26,27] Though much work has been done, there are still considerable inconsistencies.…”
Section: Introductionmentioning
confidence: 99%